Preparation method and application of biomass porous carbon for supercapacitor

By mixing the glucose solution with biomass waste powder and performing high-temperature carbonization and activation treatment, a graded porous carbon material with excellent electrochemical properties was prepared, which solved the problems of raw materials import, high cost and low electrochemical properties in the prior art. It realizes efficient recycling and environmentally friendly supercapacitor electrode material production.

CN119390067APending Publication Date: 2025-02-07SOUTH CHINA UNIV OF TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411428770.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the raw materials of graded porous carbon materials are mostly imported products, with high production costs and long production time. The porous carbon materials produced are too large in size and incomplete in space utilization, resulting in low electrochemical performance. At the same time, my country has not completely recycled passion fruit peels and pomaces.

Method used

Soaking biomass waste powder, especially passion fruit peel powder, through glucose solution, a porous carbon material with a rich number of micropores is produced. The method includes mixing the biomass waste powder with a glucose solution, drying and dehydrating, and then performing high-temperature carbonization and alkaline activation treatment to obtain a graded porous carbon.

Benefits of technology

The prepared supercapacitor electrode has good charging and discharging performance, a large specific capacity, and a significantly longer charging and discharging time, which is significantly better than the porous carbon electrode prepared from separate raw materials. This method efficiently recycles and utilizes common domestic biomass waste, meets environmental protection requirements, has a simple process, and helps reduce costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390067A_ABST
    Figure CN119390067A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of biomass porous carbon for a supercapacitor electrode, which is prepared by mixing biomass waste and glucose and then carbonizing, and comprises the following steps: washing the biomass waste, drying, then mechanically crushing and sieving to obtain biomass waste powder; mixing the biomass waste powder with a glucose solution, uniformly stirring, drying and dehydrating; the mixed powder is washed and dried after being subjected to high-temperature carbonization treatment, and pre-carbide is obtained; mixing the pre-carbide with an alkaline activator, drying, performing high-temperature carbonization activation, and washing and drying after activation to obtain a target product. Domestic common biomass waste is efficiently recycled, biomass waste powder, especially passion fruit peel powder, is soaked in a glucose solution to prepare the porous carbon material with abundant micropores, and a supercapacitor electrode prepared from the carbon material has good charge and discharge performance, large specific capacity and obviously prolonged charge and discharge time, and has a good application prospect. The porous carbon electrode is obviously superior to a porous carbon electrode prepared from a single raw material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid waste treatment and electrochemical technology, and in particular to a method for preparing biomass waste and glucose mixed graded porous carbon for supercapacitors. Background Art

[0002] The progress of human society is inseparable from the development of energy technology. Energy storage equipment plays an irreplaceable role in the energy field. Supercapacitors have the characteristics of instantaneous large current, fast charging and discharging, long cycle life, maintenance-free, and excellent safety performance. They are widely used in new energy electric vehicles, power tools, auxiliary power supplies for solar and wind power generation devices, mechanical equipment, and instrumentation. They play an important role in the development of science and technology. Therefore, it is necessary to develop high-performance supercapacitors to promote the advancement of science and technology.

[0003] Supercapacitors, also known as electrochemical capacitors, are a new type of energy storage device that is different from traditional capacitors and batteries. Supercapacitors can be divided into three categories according to the energy storage principle: electric double layer capacitors (EDLCs), Faraday pseudocapacitors, and hybrid capacitors. Electric double layer capacitors store energy based on the charge separation between electrodes and electrolytes. The ions in the electrolyte migrate in the pores of porous carbon materials to form a double layer structure, just like the two plates in traditional capacitors. When the electrodes are connected to an external power source, the anions and cations in the electrolyte solution will accumulate in the pores of the porous activated carbon corresponding to the positive and negative plates under the action of the electric field force and the Coulomb force, and thus a double layer is generated to store energy (charging). When the capacitor is connected to an external power load, the charge accumulated on the electrode is supplied to the external power circuit in the form of current (discharging). The charging and discharging process of supercapacitors is achieved by the electrostatic physical adsorption and desorption of anions and cations, rather than the chemical reaction of lithium-carbon alloy formed by desorption from the positive electrode to the graphite negative electrode like lithium batteries. Therefore, its cycle life and power density are better than lithium-ion batteries.

[0004] Faraday pseudocapacitor, also known as Faraday quasi-capacitor, is a two-dimensional or three-dimensional space in the living phase of the electrode surface where the electroactive material undergoes underpotential deposition, and a highly reversible chemical adsorption or redox reaction occurs, producing a capacitance related to the electrode charge potential. The voltage of this electrode system changes linearly with the amount of charge transfer, showing capacitance characteristics, so it is called "quasi-capacitor", which is a supplementary form of double-layer capacitor. The charging and discharging mechanism of Faraday pseudocapacitor is: the ions (usually H+ or OH-) in the electrolyte diffuse into the solution to the electrode / solution interface under the action of an external electric field, and then enter the bulk phase of the active oxide on the electrode surface through the electrochemical reaction of the interface; if the electrode material is an oxide with a large specific surface area, there will be quite a lot of such electrochemical reactions, and a large amount of charge will be stored in the electrode. During discharge, these ions that enter the oxide will return to the electrolyte, and the stored charge will be released through the external circuit.

[0005] In a hybrid supercapacitor, one electrode uses a traditional battery electrode to store and convert energy through electrochemical reactions, while the other electrode stores energy through a double layer. For both double-layer capacitors and hybrid capacitors, electrode materials are one of the most important raw materials.

[0006] At present, among the supercapacitor electrode materials, carbon materials are the most mature in industrial application because they have the advantages of acid and alkali resistance, no reaction with electrolyte, large specific surface area, low product ash content, low resistivity, wide operating temperature, good thermal stability, abundant sources, and low cost. Carbon electrode materials mainly include activated carbon, activated carbon fiber, mesoporous carbon, carbon aerogel, carbon nanotubes, graphene, etc., and supercapacitor carbon is the most successful electrode material in commercialization. Activated carbon (AC) materials have the characteristics of high density, low resistivity, rich mesoporous structure, high purity, good chemical and structural stability, and are the preferred materials for manufacturing supercapacitor electrodes. There are many raw materials for the preparation of activated carbon. Activated carbon obtained by carbonization and activation of carbon-rich materials such as phenolic resin, petroleum coke, coconut shell, sucrose, pine cones, and rice husks can be used as supercapacitor electrode materials, but different raw materials and preparation processes have a direct impact on the physical and chemical properties of activated carbon, such as specific surface area, pore structure, ash content, iron (Fe) content, and mass specific capacity. In the prior art, coconut shell carbonized material is mostly used as raw material to produce activated carbon for capacitors, but the quality of the activated carbon produced is severely limited by the origin of the raw materials, and the reaction time is long, making it difficult to effectively control the reaction rate.

[0007] Passion fruit (Passiflora edulis Sims) is a vine of the genus Passiflora in the family Passifloraceae. Its scientific name is egg fruit. It is now widely planted in tropical and subtropical regions. It is cultivated in Guangdong, Hainan, Fujian, Yunnan, Taiwan and other provinces in China. It is mainly used to make juice. In the process of juicing, thousands of tons of seeds, pulp and peel are produced as agricultural by-products. These agricultural by-products account for 60% to 70% of processed fruits, but in most cases they will be discarded, which not only wastes resources but also pollutes the environment. Therefore, it is necessary to make comprehensive use of passion fruit by-products to increase their added value.

[0008] However, the current recycling of passion fruit peels is focused on extracting edible pigments or bioactive compounds, and fruit residues still remain after the extraction, making it difficult to achieve complete recycling. Summary of the invention

[0009] In view of the fact that the raw materials of graded porous carbon materials in the prior art are mostly imported products, the production cost is high, the production time is long, and the pore size of the porous carbon material is too large, the space utilization is incomplete, and the electrochemical performance of the porous carbon is low; at the same time, my country's recycling of passion fruit peels and pomace is incomplete. The present invention provides a preparation method of biomass waste and glucose mixed graded porous carbon for supercapacitors. The method prepares a porous carbon material with abundant micropores by soaking biomass waste powder in glucose solution. The supercapacitor electrode prepared from the carbon material has good charge and discharge performance, large specific capacity, and significantly longer charge and discharge time, which is significantly better than the porous carbon electrode prepared from a single raw material; and it can efficiently recycle common domestic biomass waste to prepare porous carbon for supercapacitor electrodes, meets environmental protection requirements, has a simple process, and is helpful to reduce costs and promote application.

[0010] The technical solution of the present invention is as follows:

[0011] A method for preparing biomass porous carbon for supercapacitors comprises the following steps:

[0012] S1. The biomass waste is washed, dried, mechanically crushed, and sieved to obtain biomass waste powder;

[0013] S2. Weigh glucose and prepare a glucose solution with deionized water; mix the biomass waste powder obtained in S1 with the glucose solution, stir evenly, and then dry and dehydrate to obtain a mixed powder;

[0014] S3. The mixed powder obtained in S2 is placed in a tubular furnace, an inert protective gas is introduced, the temperature is raised to 400 to 500°C, the reaction is carried out for 1.5 to 2.5 hours for high-temperature carbonization treatment, and the product after high-temperature carbonization treatment is washed and dried to obtain a pre-carbonized product;

[0015] S4. The pre-carbonized product obtained in S3 is mixed with an alkaline activator and dried, and then placed in a tubular furnace, an inert protective gas is introduced, the temperature is raised to 700-900°C, and the reaction is performed for 1.5-2.5 hours for high-temperature carbonization activation. After activation, the pre-carbonized product is washed and dried to obtain the graded porous carbon.

[0016] Furthermore, in the above-mentioned preparation method, in step S1, the biomass waste is selected from one or more of coconut shells, bamboo, sawdust, and passion fruit peels.

[0017] Furthermore, in the above-mentioned preparation method, in step S1, the biomass waste is passion fruit peel.

[0018] Furthermore, in the above-mentioned preparation method, in step S1, washing is washing with clean water; the drying temperature is 80-120° C.; the drying time is 24-48 hours, and the sieving mesh number is 20-200 meshes.

[0019] Furthermore, in the above-mentioned preparation method, in step S1, washing is ultrasonic washing; the drying temperature is 105° C.; the drying time is 24 hours, and the sieving mesh size is 50 meshes.

[0020] Furthermore, in the above-mentioned preparation method, in step S2, the mass ratio of glucose to biomass waste powder is 1:0.5;

[0021] The biomass waste powder and the glucose solution are mixed by pouring the glucose solution into a beaker containing the biomass waste powder and stirring the mixture so that the powder is fully soaked by the glucose solution;

[0022] The drying and dehydration method is to place the mixture in a drying oven and dry it at 105°C for 24 hours.

[0023] Furthermore, in the above-mentioned preparation method, during the drying and dehydration process, the mixture is stirred once every two hours at a rotation speed of 500 rpm.

[0024] Furthermore, in the above-mentioned preparation method, in steps S3 and S4, the inert protective gas is nitrogen with a flow rate of 60 ml / min.

[0025] Furthermore, in the above-mentioned preparation method, in step S3, the high-temperature carbonization treatment temperature is 400° C., and the treatment time is 2 hours.

[0026] Further, in the above-mentioned preparation method, in step S4, the alkaline activator is KOH with a purity of 85% to 99%, and the mass ratio of the pre-carbonized material to the alkaline activator is 1:2;

[0027] The high temperature carbonization activation temperature is 800°C and the activation time is 2h;

[0028] The washing process was performed by respectively using 1M HCl, deionized water and anhydrous ethanol for cleaning and filtration. After washing, the drying temperature was 105°C and the drying time was 24 hours.

[0029] The present invention also provides an application of the hierarchical porous carbon prepared by any of the above preparation methods in preparing supercapacitor electrodes.

[0030] The beneficial effects of the present invention are as follows: the present invention prepares a porous carbon material with rich micropores by soaking biomass waste powder, especially passion fruit peel powder, in a glucose solution. The supercapacitor electrode prepared from the carbon material has good charge and discharge performance, large specific capacity, and significantly longer charge and discharge time, which is significantly better than the porous carbon electrode prepared from a single raw material, and has a significant synergistic effect. The present invention efficiently recycles common domestic biomass waste to prepare porous carbon for supercapacitor electrodes, meets environmental protection requirements, has a simple process, and helps to reduce costs and promote application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0032] Figure 1 It is a line graph of the pore size distribution of each sample in performance test example 1 of the present invention.

[0033] Figure 2 It is a comparison chart of the charge and discharge performance of electrodes prepared from various samples of performance test example 2 of the present invention. DETAILED DESCRIPTION

[0034] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.

[0035] The raw materials in the examples are all commercially available with purity meeting the requirements (>99.5%), reagents, solvents, etc. are all of chromatographic grade, and intermediate samples are homemade products and purchased from the market; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0036] Unless otherwise specified, the following terms and phrases used herein are intended to have the following meanings. A particular phrase or term should not be considered to be uncertain or unclear in the absence of a special definition, but should be understood according to its ordinary meaning. When a trade name appears in this article, it is intended to refer to its corresponding commercial product or its active ingredient.

[0037] The present invention will be specifically described below by examples, which are not intended to limit the present invention. It will be appreciated by those skilled in the art that these examples are intended to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for the unrecorded specific conditions in the following examples are usually performed under normal conditions or according to the conditions recommended by the manufacturer. Unless otherwise indicated, percentages and parts are calculated by weight. The following examples are primarily intended to better understand the analytical method of the present invention and are not intended to exhaust all modes of operation.

[0038] Example 1

[0039] S1. Wash the passion fruit peel with deionized water, dry it in a forced air drying oven at 105°C for 24 h, and then grind it into powder in a grinder and pass it through a 50-mesh sieve.

[0040] S2. Use an analytical balance to weigh 0.5 times the mass of glucose of the passion fruit peel powder, first dissolve the glucose with deionized water, then pour the glucose solution into the beaker containing the passion fruit peel powder and stir thoroughly; put the stirred mixture into a forced air drying oven, dry it at 105°C for 24 hours, and stir it every two hours.

[0041] S3. The mixed powder obtained in step S2 is placed in a corundum boat, and placed in a tubular furnace for pre-carbonization. The pre-carbonization conditions are as follows: in a protective atmosphere with a N2 flow rate of 60 ml / min, heat to 400°C at a heating rate of 5°C / min, keep warm for 2 hours, and take out the product after the tubular furnace is cooled to room temperature, while continuously introducing N2; the product is immersed in deionized water for ultrasonic washing for 10 minutes, and then filtered, and the above washing method is repeated three times. The obtained product is placed in a forced air drying oven and dried at 105°C for 24 hours to obtain a pre-carbonized product.

[0042] S4. Use an analytical balance to weigh KOH with a purity of 85% which is twice the mass of the pre-carbide obtained in S3, and place it and the pre-carbide in a grinding mortar for thorough grinding; put the ground mixture into a corundum boat, and place it in a tubular furnace for high-temperature activation. The high-temperature activation conditions are: in a protective atmosphere with a N2 flow rate of 60 ml / min, heat to 800°C at a heating rate of 5°C / min, keep warm for 2 hours, and take out the product after the tubular furnace cools to room temperature, while continuously passing N2 during this period.

[0043] S5. The product obtained in S4 is immersed in 1M HCl until the pH of the solution is acidic, and then ultrasonically washed for 20 minutes, and then ultrasonically washed with deionized water and ethanol for 10 minutes in turn, and then filtered until the pH of the washing solution is 7. The obtained product is placed in a forced air drying oven and dried at 105°C for 24 hours to obtain the target product, graded porous carbon PGC1-0.5.

[0044] Example 2

[0045] S1. Wash the passion fruit peel with deionized water, dry it in a forced air drying oven at 105°C for 24 h, and then grind it into powder in a grinder and pass it through a 50-mesh sieve.

[0046] S2. Use an analytical balance to weigh glucose that is 1 times the mass of the passion fruit peel powder, first dissolve the glucose in deionized water, then pour the glucose solution into a beaker containing the passion fruit peel powder and stir thoroughly; put the stirred mixture into a forced air drying oven, dry it at 105°C for 24 hours, and stir it every two hours.

[0047] S3. The mixed powder obtained in step S2 is placed in a corundum boat, and placed in a tubular furnace for pre-carbonization. The pre-carbonization conditions are as follows: in a protective atmosphere with a N2 flow rate of 60 ml / min, heat to 400°C at a heating rate of 5°C / min, keep warm for 2 hours, and take out the product after the tubular furnace is cooled to room temperature, while continuously introducing N2; the product is immersed in deionized water for ultrasonic washing for 10 minutes, and then filtered, and the above washing method is repeated three times. The obtained product is placed in a forced air drying oven and dried at 105°C for 24 hours to obtain a pre-carbonized product.

[0048] S4. Use an analytical balance to weigh KOH with a purity of 85% which is twice the mass of the pre-carbide, and place it and the pre-carbide in a grinding mortar for thorough grinding; put the ground mixture into a corundum boat, and place it in a tubular furnace for high-temperature activation. The high-temperature activation conditions are: in a protective atmosphere with a N2 flow rate of 60 ml / min, heat to 800°C at a heating rate of 5°C / min, keep warm for 2 hours, and take out the product after the tubular furnace cools to room temperature, while continuously passing N2 during this period.

[0049] S5. The product obtained in S4 is immersed in 1M HCl until the pH of the solution is acidic, and then ultrasonically washed for 20 minutes, and then ultrasonically washed with deionized water and ethanol for 10 minutes in turn, and then filtered until the pH of the washing solution is 7. The obtained product is placed in a forced air drying oven and dried at 105°C for 24 hours to obtain the target product, hierarchical porous carbon PGC1-1.

[0050] Example 3

[0051] S1. Wash the passion fruit peel with deionized water, dry it in a forced air drying oven at 105°C for 24 h, and then grind it into powder in a grinder and pass it through a 50-mesh sieve.

[0052] S2. Use an analytical balance to weigh glucose twice the mass of passion fruit peel powder, first dissolve the glucose in deionized water, then pour the glucose solution into a beaker containing passion fruit peel powder and stir thoroughly; place the mixture obtained in step (2) in a forced air drying oven and dry it at 105°C for 24 hours, stirring every two hours.

[0053] S3. The mixed powder obtained in S2 is placed in a corundum boat and placed in a tubular furnace for pre-carbonization. The pre-carbonization conditions are as follows: in a protective atmosphere with a N2 flow rate of 60 ml / min, heat to 400°C at a heating rate of 5°C / min, keep warm for 2 hours, cool the tubular furnace to room temperature and then take out the product, while continuously passing N2; the product is immersed in deionized water for ultrasonic washing for 10 minutes, then filtered, and the above washing method is repeated three times. The obtained product is placed in a forced air drying oven and dried at 105°C for 24 hours to obtain a pre-carbonized product.

[0054] S4. Use an analytical balance to weigh KOH with a purity of 85% which is twice the mass of the pre-carbide, and place it and the pre-carbide in a grinding mortar for thorough grinding; put the ground mixture into a corundum boat, and place it in a tubular furnace for high-temperature activation. The high-temperature activation conditions are: in a protective atmosphere with a N2 flow rate of 60 ml / min, heat to 800°C at a heating rate of 5°C / min, keep warm for 2 hours, and take out the product after the tubular furnace cools to room temperature, while continuously passing N2 during this period.

[0055] S5. The product obtained in S4 is immersed in 1M HCl until the pH of the solution is acidic, and then ultrasonically washed for 20 minutes, and then ultrasonically washed with deionized water and ethanol for 10 minutes in turn, and then filtered until the pH of the washing solution is 7. The obtained product is placed in a forced air drying oven and dried at 105°C for 24 hours to obtain the target product, hierarchical porous carbon PGC1-2.

[0056] Comparative Example 1

[0057] S1. Wash the passion fruit peel with deionized water, dry it in a forced air drying oven at 105°C for 24 h, and then grind it into powder in a grinder and pass it through a 50-mesh sieve.

[0058] S2. Put the passion fruit peel powder into a corundum boat and place it in a tubular furnace for pre-carbonization. The pre-carbonization conditions are as follows: heat to 400°C at a heating rate of 5°C / min in a protective atmosphere with a N2 flow rate of 60 ml / min, keep warm for 2 hours, cool the tubular furnace to room temperature and then take out the product, while continuously passing N2; immerse the product in deionized water for ultrasonic washing for 10 minutes, then filter and repeat the above washing method three times, put the obtained product into a forced air drying oven, and dry it at 105°C for 24 hours to obtain a pre-carbonized product.

[0059] S3. Use an analytical balance to weigh KOH with a purity of 95% which is twice the mass of the pre-carbide, and place it and the pre-carbide in a grinding mortar for thorough grinding; put the ground mixture into a corundum boat, and place it in a tubular furnace for high-temperature activation. The high-temperature activation conditions are: in a protective atmosphere with a N2 flow rate of 60 ml / min, heat to 800°C at a heating rate of 5°C / min, keep warm for 2 hours, and take out the product after the tubular furnace cools to room temperature, while continuously passing N2 during this period.

[0060] S4. The product obtained in S3 was immersed in 1M HCl until the pH of the solution was acidic, and then ultrasonically washed for 20 minutes, and then ultrasonically washed with deionized water and ethanol for 10 minutes in turn, and then filtered until the pH of the washing solution was 7. The obtained product was placed in a forced air drying oven and dried at 105°C for 24 hours to obtain the final product PGC1-0.

[0061] Comparative Example 2

[0062] S1. Put glucose into a corundum boat and place it in a tubular furnace for pre-carbonization. The pre-carbonization conditions are as follows: heat to 400°C at a heating rate of 5°C / min in a protective atmosphere with a N2 flow rate of 60 ml / min, keep warm for 2 hours, take out the product after the tubular furnace cools to room temperature, and continuously introduce N2 during this period; immerse the product in deionized water for ultrasonic washing for 10 minutes, then filter and repeat the above washing method three times, put the obtained product into a forced air drying oven, and dry it at 105°C for 24 hours to obtain a pre-carbonized product.

[0063] S2. Use an analytical balance to weigh 95% pure KOH twice the mass of the pre-carbide, and place it and the pre-carbide in a grinding mortar for thorough grinding; put the ground pre-carbide into a corundum boat, and place it in a tubular furnace for high-temperature activation. The high-temperature activation conditions are: in a protective atmosphere with a N2 flow rate of 60 ml / min, heat to 800°C at a heating rate of 5°C / min, keep warm for 2 hours, and take out the product after the tubular furnace cools to room temperature, while continuously passing N2 during this period.

[0064] S3. The product obtained in S2 was immersed in 1M HCl until the pH of the solution was acidic, and then ultrasonically washed for 20 minutes, and then ultrasonically washed with deionized water and ethanol for 10 minutes in turn, and then filtered until the pH of the washing solution was 7. The obtained product was placed in a forced air drying oven and dried at 105°C for 24 hours to obtain the final product PGC0-1.

[0065] Performance Testing

[0066] 1. Porous carbon product pore size determination

[0067] The pore sizes of the porous carbon products prepared in each embodiment and comparative example were measured by nitrogen adsorption-desorption test. Figure 1It is the pore size distribution diagram of each embodiment and comparative example sample. As shown in the figure, the porous carbon products prepared in each embodiment have abundant micropores, and the micropore diameters are mainly distributed around 0.85nm. The number of micropores in sample PGC1-0.5 is particularly large; the micropore diameters of sample PGC1-0 prepared in comparative example 1 are mainly distributed at 2nm, and the number of micropores of sample PGC0-1 prepared in comparative example 2 is less than that of each embodiment and comparative example 1 as a whole. The pore size distribution broken line of the material obtained by mixing PGC1-0 and PGC0-1 (broken line 1-0 / 0-1) is similar to the curves of each embodiment, but is still inferior to PGC1-0.5. The above results prove that the filling of glucose can change the pore size distribution of porous carbon, and the pore size of porous carbon materials can be effectively adjusted in combination with the activation of KOH.

[0068] 2. Electrochemical performance test of supercapacitor electrodes made from porous carbon products

[0069] The porous carbon supercapacitor electrode preparation method is as follows:

[0070] (1) The porous carbon product, conductive carbon black and 65% PTFE emulsion are mixed in a mass percentage ratio of 8:1:1, ethanol is added to form a slurry, and the slurry is heated and stirred until the ethanol is semi-dry and in a muddy state;

[0071] (2) The material obtained in step (1) was transferred to a glass plate, and the glass plate was repeatedly rolled into a thin slice, and then the thin slice was removed using a 1 cm*1 cm square cutting mold;

[0072] (3) The thin sheet obtained in step (2) is pressed onto a 1 cm*1 cm square nickel foam using a powder press at a pressure of 6 MPa, and finally the pressed electrode is dried in a vacuum drying oven at 80° C. for 12 h to finally obtain an electrode made of porous carbon.

[0073] Electrochemical performance test of electrode sheet:

[0074] The prepared electrode sheet was used with 6M KOH as the electrolyte, and its electrochemical performance was tested using a CHI660E electrochemical workstation.

[0075] Figure 2 The charge and discharge performance comparison of each embodiment and comparative example sample under a current density of 0.1A / g in a three-electrode system shows that all samples have almost symmetrical isosceles triangles, indicating that the porous carbon electrode sheets prepared in each embodiment and comparative example have good reversibility during the charge and discharge process, which is consistent with the charge and discharge characteristics of supercapacitors; at the same time, it can be intuitively seen that after adding glucose, the porous carbon has a significantly longer charge and discharge time due to the rich pore structure on the surface, indicating that it has a larger capacity. By calculation, it can also be known that the specific capacity of PGC1-0.5 is 278F / g, which is greater than that of the sample PGC1-0 without adding glucose.

[0076] (236.3F / g) and pure glucose carbonization activated PGC0-1 (252.1F / g), achieving the effect of "one plus one is greater than two".

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing biomass porous carbon for supercapacitor electrodes, comprising the following steps: S1. The biomass waste is washed, dried, mechanically crushed, and sieved to obtain biomass waste powder; S2. Weigh glucose and prepare a glucose solution with deionized water; mix the biomass waste powder obtained in S1 with the glucose solution, stir evenly, and then dry and dehydrate to obtain a mixed powder; S3. Place the mixed powder obtained in S2 in a tube furnace, introduce inert protective gas, and heat to 400-500°C, react for 1.5-2.5h to perform high temperature carbonization treatment, wash and dry the product after the high temperature carbonization treatment to obtain a pre-carbonized product; S4. The pre-carbonized product obtained in S3 is mixed with an alkaline activator and dried, and then placed in a tubular furnace, an inert protective gas is introduced, the temperature is raised to 700-900°C, and the reaction is performed for 1.5-2.5 hours for high-temperature carbonization activation. After activation, the pre-carbonized product is washed and dried to obtain the graded porous carbon.

2. The preparation method according to claim 1, characterized in that: In step S1, the biomass waste is selected from one or more of coconut shells, bamboo, wood chips, and passion fruit peels.

3. The preparation method according to claim 2, characterized in that: In step S1, the biomass waste is passion fruit peel.

4. The preparation method according to claim 1, characterized in that: In step S1, washing is performed with clean water; the drying temperature is 80-120° C.; the drying time is 24-48 hours, and the sieving mesh number is 20-200 meshes.

5. The preparation method according to claim 3, characterized in that: In step S1, washing is ultrasonic washing; the drying temperature is 105° C.; the drying time is 24 hours, and the sieving mesh size is 50 meshes.

6. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the glucose to the biomass waste powder is 1:0.5; The biomass waste powder and the glucose solution are mixed by pouring the glucose solution into a beaker containing the biomass waste powder and stirring the mixture so that the powder is fully soaked in the glucose solution; The drying and dehydration method is to place the mixture in a drying oven and dry it at 105° C. for 24 hours.

7. The preparation method according to claim 5, characterized in that: During the drying and dehydration process, the mixture was stirred once every two hours at a rotation speed of 500 rpm.

8. The preparation method according to claim 1, characterized in that: In steps S3 and S4, the inert protective gas is nitrogen with a flow rate of 60 ml / min.

9. The preparation method according to claim 1, characterized in that: In step S3, the high temperature carbonization treatment temperature is 400° C. and the treatment time is 2 h.

10. The preparation method according to claim 1, characterized in that: In step S4, the alkaline activator is KOH with a purity of 85% to 99%, and the mass ratio of the pre-carbonized material to the alkaline activator is 1:2; The high temperature carbonization activation temperature is 800°C and the activation time is 2h; The washing is performed by using 1M HCl, deionized water and anhydrous ethanol for cleaning and filtration respectively. The drying temperature after washing is 105° C. and the drying time is 24 hours.

11. Use of the hierarchical porous carbon prepared by the preparation method according to any one of claims 1 to 10 in preparing supercapacitor electrodes.

Citation Information

Cited By

  • Method for preparing porous carbon material from aldose-saccharide compound, porous carbon material and application

    CN120057893A

  • Method for preparing porous carbon by regulating and controlling biomass structure through saccharides and application of porous carbon

    CN121085269A